2019
DOI: 10.3171/2017.12.jns172331
|View full text |Cite
|
Sign up to set email alerts
|

Rates and predictors of seizure outcome after corpus callosotomy for drug-resistant epilepsy: a meta-analysis

Abstract: OBJECTIVE Corpus callosotomy is a palliative surgery for drug-resistant epilepsy that reduces the severity and frequency of generalized seizures by disconnecting the two cerebral hemispheres. Unlike with resection, seizure outcomes remain poorly understood. The authors systematically reviewed the literature and performed a meta-analysis to investigate rates and predictors of complete seizure freedom and freedom from drop attacks after corpus callosotomy. METHODS PubMed, Web of Science, and Scopus were queried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
1
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 83 publications
4
61
1
11
Order By: Relevance
“…Total callosotomy yields favorable outcome in drop attacks' freedom compared to partial callosotomy. 7 Our observation showed that 5 of 9 patients with total callosotomy achieved complete seizure freedom compared to 1 of 7 partial callosotomy patients. A study in drop attacks patient demonstrated that the seizure-free rate in total and partial callosotomy was 90% and 54% respectively during a 7-year follow-up.…”
Section: Discussionmentioning
confidence: 52%
“…Total callosotomy yields favorable outcome in drop attacks' freedom compared to partial callosotomy. 7 Our observation showed that 5 of 9 patients with total callosotomy achieved complete seizure freedom compared to 1 of 7 partial callosotomy patients. A study in drop attacks patient demonstrated that the seizure-free rate in total and partial callosotomy was 90% and 54% respectively during a 7-year follow-up.…”
Section: Discussionmentioning
confidence: 52%
“…1,26 However, the relationship between the location of interhemispheric FC reduction and seizure outcome is rarely studied. Traditionally, callosotomy targets the anterior corpus callosum; complete callosotomy is already known to be more associated with complete seizure freedom and drop attack freedom than partial callosotomy.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, callosotomy targets the anterior corpus callosum; complete callosotomy is already known to be more associated with complete seizure freedom and drop attack freedom than partial callosotomy. 1,26 However, the relationship between the location of interhemispheric FC reduction and seizure outcome is rarely studied. A recent interesting study by Paglioli et al raised the possibility that posterior callosotomy may achieve outcomes in epileptic fall reduction comparable to those of total callosotomy because the crossing fibers from the premotor and primary motor cortex are posteriorly located in the mid to posterior half of corpus callosum.…”
Section: Discussionmentioning
confidence: 99%
“…Complete seizure freedom was achieved in 20% of patients. 99 Adverse events were rare, and neurologic deficits including lower-extremity weakness or speech problems occurred in 14.3% of patients. 97…”
Section: Corpus Callosotomymentioning
confidence: 99%